Differences in Rural and Urban Health Information Access and Use - Chen, Xuewei; Orom, Heather; Hay, Jennifer L.; Waters, Erika A.; Schofield, Elizabeth; Li, Yuelin; Kiviniemi, Marc T. (The Journal of rural health, 2019)
Purpose Rural residents may have lower access to and use of certain health information sources relative to urban residents. We investigated differences in information source access and use between rural and urban US adults and whether having low health literacy might exacerbate rural disparities in access to and use of health information. Methods Six hundred participants (50% rural) completed an online survey about access and use of 25 health information sources. We used logistic regression models to test associations between rurality and access to and use of health information sources and whether rurality interacted with health literacy to predict the access and use. Findings Compared to urban residents, rural residents had lower access to health information from sources including primary care providers, specialist doctors, blogs, and magazines, and less use of search engines. After accounting for sociodemographics, rural residents only had lower access to specialist doctors than urban residents. Rural residents with limited health literacy had lower access to mass media and scientific literature but higher use of corporations/companies than rural residents with adequate health literacy and urban residents regardless of health literacy level. Conclusions Some differences in access to and use of health information sources may be accounted for by sociodemographic differences between rural and urban populations. There may be structural barriers such as shortage of specialist doctors and limited media exposure that make it harder for rural residents to access health information, especially those with limited health literacy.